HISTORICAL-PHILOSOPHICAL ESSENCE OF THE CONCEPT OF PATRIOTISM (Scientific journal of the Fergana State University, 2024)
This article analyzes the essence of the concept of patriotism, the fact that patriotism as a phenomenon of social consciousness functions only under the conditions of internationalism and nationalism, and is considered as a complex dynamic system. It is emphasized that patriotism is expressed and manifested in various forms.